SPECIFICS OF HEDGE ACCOUNTING IN ORGANIZATIONS - Gerasimova, Larisa (Revista Inclusiones, 2020)
The hedge accounting principles established by International Financial Reporting Standards are analyzed in the article. It shows that their application will ensure uniformity of approaches both for Russian and international standards of reporting. The main principle of hedge accounting is analyzed, according to which, financial results (and/or cash flows) related to the hedging instrument and hedged transaction, caused by hedged risk, are accounted for simultaneously. It has been considered what may be an instrument and object of hedging in organizations. The article demonstrates the conditions under which an organization may engage in hedge accounting. The rules of hedge accounting in hedges of fair value and cash flows have been disclosed. Examples of fair value hedges and future cash flow hedges are provided. The criteria for derecognition of an asset are described.